21 Young Scholar Talk PHD: Effects of Pre-Transportation Feeding Program on Intake, Body Weight Loss, Rumen Fermentation, and Physiological Responses of Receiving Feedlot Cattle. (22nd October 2022) - Figueroa-Zamudio, Joaquin J; Birkenstock, Bianca; Sanchez-Sandoval, Ulises A; Smythe, Brandon G; Gouvêa, Vinicius N; Löest, Clint A; Soto-Navarro, Sergio A
Abstract: This study evaluated the effects of preconditioning diet management and transportation on performance, rumen pH, and rectal temperature of feedlot receiving cattle. Twenty rumen cannulated angus heifers (758 ± 50.7 lb) were used in a complete randomized design with a 2×2 factorial arrangement of treatments with repeated measures related to time of transportation. One factor was the preconditioning diet management consisting on offering a preconditioning diet for the 30 days prior to transportation (diet), or offer the same diet for 27 days and the last 3 days prior to transportation received only hay (hay). The second factor was transportation and consisted of transporting or not transporting the heifers for 12 hours. All heifers received a commercial feedlot receiving diet at arrival and for 14 days. Measurements were obtained at 92 and 20 h before transportation, at 0 (right before loading for transportation), 6, 12, 78, 76, 172, 340 h after transportation. All the sampling points but 0, 6 and 12 h were 4 h after feeding or around peak of fermentation. Performance, rectal temperature and ruminal pH were analyzed using MIXED procedures. Rectal temperature, rumen pH, intake presented diet×time interactions. Rectal temperature was greater (P = 0.02) for hay at time 0 and no effects at other times (P > 0.10). Rumen pH was greater (P = 0.01) at 20 h prior and at 76 h after, and lower (P = 0.05) at 340 h after transportation for hay than diet and no effects at the rest of the time points. Intake was lower (P ≤ 0.05) at 20 h prior and 76 and 172 h after transportation for hay than for diet. In conclusion, changing the preconditioning diet to hay only prior transportation had detrimental effects on rumen fermentation characteristics and intake of the receiving diet. Such dietary changes might have switched the rumen bacterial population to more cellulolytic bacteria. Findings of this experiment suggest the needs of further research that assesses the effect of manipulating the diet right before transportation.